Bosch Osteotomy for Hallux Valgus Correction: Results at a Mean 10-Year Follow-Up. Issue 1 (January 2022) - Bernasconi, Alessio; Rizzo, Maria; Russo, Anna Paola; Vallefuoco, Salvatore; Guarino, Amedeo; Mariconda, Massimo
Category: Bunion; Midfoot/Forefoot Introduction/Purpose: Boesh osteotomy (BO) is a surgical option for the correction of hallux valgus (HV). The aim of this study was to assess the long-term clinical and radiographic results in a cohort of patients treated at our institution. Methods: In this retrospective cohort study, we included 58 HVs (28 right, 30 left) in 46 patients (42 females, 4 males; mean age and BMI at surgery 44 +- 15 (range, 15-64) years and 26 +- 4 (range, 22-38) points, respectively) who underwent HV correction by BO and were followed at a minimum of 7 years. The range of motion (ROM), the American Orthopaedic Foot & Ankle Society's Forefoot scale (AOFAS-FS) and the Visual Analogic Scale (VAS) for pain were recorded. On weightbearing radiographs, the Hallux Valgus Angle (HVA), Intermetatarsal Angle (IMA), the Distal Metatarsal Articular Angle (DMAA) and the Sesamoid position were measured and compared with pre-operative values. The complication rate and first metatarsophalangeal joint stiffness were also assessed. Results: At a mean follow-up of 10+-2 (range, 7-17) years, mean+-standard deviation AOFAS-FS and VAS were 89+-11 (range, 67-93) and 2.1+-2.8 (range, 0-7) points, respectively. In 62% of patients there was no pain while in 38% an occasional pain was referred. In 42 (72%) cases there was no limitation in the choice of footwears. Radiographically, we found a significant improvement in the HVA (from 33.9°+-6.7 to 18.8°+-5.6, p<0.001), in the IMA (14.2°+-3.1 to 9.4°+-2.7, p<0.001), in the DMAA (from 30.3°+-6.8 to 11.5°+-5.1, p<0.001) and in the sesamoid position (median value from 3 to 1, p<0.001). In 36 (62%) cases the ROM was greater than 75° while in 22 (38%) it ranged between 30° and 75°. Complications occurred in 6 (10%) cases (3 superficial infections, 1 accidental removal of the K-wire, 1 metatarsal head necrosis and 1 development of osteoarthritis), which did not require any surgery at the longest follow-up. Conclusion: Boesh technique provided satisfactory clinical and radiographic outcomes in the correction of Hallux Valgus which persisted at a mean 10-year follow-up. The complication rate was not different from more recent techniques described in literature.